BRIDGE AS A DOMINATE TECHNICAL STRUCTURE IN THE WRESTLING OF GREEK AND ROMAN AND FREE STYLE - Mališa Radović; Goran Kasum (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Wrestling belongs to the group of very complex, semistructual, non-rhytmical sports. Process of achieving the top sport's results is more and more based on scientifi c methods of researching by discovering an establishing the factors from those the success in sport is depended, and from the other side establishing the effects of sports on structure of person. The objective guarantee in achieving the top of sports results is possible only with maximum connections between sport and factors of persons, as also as discovering the measure instruments which are used to fi nd out the development of these factors. The wrestling is specifi c for differences and many technical elements, strategy, movements of body which use the complex physical capabilities. Including the questionnaire of great sportsmen and trainers, there are opinions which are connected with wrestling bridge as important technical for realization of results. Using the questionnaire paper, we collected the opinions of 218 wrestlers and 98 trainers for Greece -roman and Free Style. These opinions and attitude of sportsmen and trainers give basis for next researching when it is talk about the importance of wrestling bridge